Perception on women empowerment in administration: a study at rubber industry smallholders development authority (RISDA), Kuala Lumpur / Muhammad Amir Asraf Hasagaya and Liyana Jamaluddin - Hasagaya, Muhammad Amir Asraf; Jamaluddin, Liyana (Faculty of Administrative Science and Policy Studies, 2013)
This paper analyzes multiple factors on the perception of employees on women empowerment in administration. Empowerment can be defined on various dimensions such as on economic empowerment, human and social empowerment, political empowerment and also cultural empowerment. Women empowerment can be defined as the idea to focus on the feminine and manifestation of womanhood with a main goal to bring perfect balance between the men and the women in the nature of forces irrespective of gender. It can also be understood as the concept of women to have the capacity to act, to organise and change existing hierarchies. It also mean that women in an organisation to have increased role in decision making and bargaining power. The study focuses on the factors that may influence employees’ perception regarding women empowerment in administration. Some of the factors are demographic factors, culture, and also policies. It is important to understand the psychology of perceptions and perspectives so that top managers can better manage their employees inside the administration environment.